A Complete 16 μm Selected Galaxy Sample at z ∼ 1. II. Morphological Analysis - Liang, Piaoran; Dai, Y. Sophia; Huang, Jia-Sheng; Cheng, Cheng; Shi, Yaru (The Astrophysical journal, 2024)
We present a morphological analysis of the 16 μ m flux-density-limited galaxy sample at 0.8 < z < 1.3 from Huang et al. (2021). At the targeted redshift, the 16 μ m emission corresponds to the polycyclic aromatic hydrocarbon feature from intense star formation, or dust heated by active galactic nuclei (AGN). Our sample of 479 galaxies are dominated by luminous infrared galaxies (LIRGs; 67%) in three CANDLES fields (Extended Groth Strip, ​​​​Great Observatories Origins Deep Survey North and South fields), and are further divided into AGN-dominated, star-forming dominated, composite, and blue compact galaxies by their spectral energy distribution types. The majority of our sample (71%) have disk morphologies, with the few AGN-dominated galaxies being more bulge-dominated than the star-forming-dominated and composite galaxies. The distribution of our sample on the Gini versus M 20 plane is consistent with previous studies, where the Sérsic index n shows an increasing trend toward the smaller M 20 and higher Gini region below the dividing line for mergers. The subsample of ultraluminous infrared galaxies (ULIRGs) follows a steep size–mass relation that is closer to the early-type galaxies. In addition, as the 4.5 μ m luminosity excess ( L 4.5 exc , proxy for AGN strength) increases, our sample appears to be more bulge dominated (i.e., higher n ). Based on the specific star formation rate and compactness ( log 10 Σ 1.5 , Σ 1.5 = M * / R e 1.5 ) diagram, the majority of our LIRG-dominated galaxy sample follows a secular evolution track, and their distribution can be explained without involving any merging activities. Out of the 16 ULIRGs in our sample, six are compact with strong AGN contributions, likely evolving along the fast track from more violent activities.